(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The economy of India mainly based on the growth of financial sector which is been supported by Both Private & Private Sector Banks in India. Nowadays It has been affected by NPA’s. In the last decade, Indian banks made headlines often with the mounting NPAs (Non-Performing Assets) and the following mergers. Modern banks are increasingly focusing on a business stream distinct from traditional banking, which enables them to reduce their risk portfolio and maximize the efficiency of their labor and resources. When an asset does not create any income for the bank, it is referred to as a non-performing asset (NPA). The loans granted to customers are the bank's assets. The loan becomes a Bad Loan or Non-Performing Asset if the consumer does not pay either the interest or the principal. We conclude by drawing policy lessons from this discussion and suggest some measures that can be adopted to better deal with a future balance sheet related crisis in the banking sector such that the impact on the real economy is minimal.